2017
DOI: 10.2147/cpaa.s144606
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of pomalidomide in patients with relapsed or refractory multiple myeloma with various degrees of impaired renal function

Abstract: Pomalidomide is an immunomodulatory drug for treatment of relapsed or refractory multiple myeloma (rrMM) in patients who often have comorbid renal conditions. To assess the impact of renal impairment on pomalidomide exposure, a population pharmacokinetics (PPK) model of pomalidomide in rrMM patients with various degrees of impaired renal function was developed. Intensive and sparse pomalidomide concentration data collected from two clinical studies in rrMM patients with normal renal function, moderately impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…13 The pharmacokinetics (PK) of pomalidomide after a single oral dose of 4 mg in plasma was characterized by rapid absorption (median time to peak plasma drug concentration [t max ] 2.50-3.25 hours post dose) and rapid elimination (mean terminal half-life [t 1/2 ] range of 8.90-11.21 hours). Consistently, several studies showed that the PK of pomalidomide was not remarkably affected in renally impaired patients, 17,18 and the liver plays the predominant role in eliminating pomalidomide in vivo. Human [ 14 C]pomalidomide absorption, metabolism, and excretion study showed that the recovery of total [ 14 C]radioactivity was approximately 88% of the administered dose, with 72.8% and 15.5% recovered in urine and feces, respectively.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…13 The pharmacokinetics (PK) of pomalidomide after a single oral dose of 4 mg in plasma was characterized by rapid absorption (median time to peak plasma drug concentration [t max ] 2.50-3.25 hours post dose) and rapid elimination (mean terminal half-life [t 1/2 ] range of 8.90-11.21 hours). Consistently, several studies showed that the PK of pomalidomide was not remarkably affected in renally impaired patients, 17,18 and the liver plays the predominant role in eliminating pomalidomide in vivo. Human [ 14 C]pomalidomide absorption, metabolism, and excretion study showed that the recovery of total [ 14 C]radioactivity was approximately 88% of the administered dose, with 72.8% and 15.5% recovered in urine and feces, respectively.…”
supporting
confidence: 54%
“…In addition to pomalidomide, 4 metabolites were detected in fecal extracts. Consistently, several studies showed that the PK of pomalidomide was not remarkably affected in renally impaired patients, 17,18 and the liver plays the predominant role in eliminating pomalidomide in vivo.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Pomalidomide pharmacokinetics have been well characterized both in healthy subjects and in subjects with relapsed and refractory MM . Pomalidomide was absorbed with a maximum plasma concentration (C max ) at a median time (t max ) between 2.0 and 3.0 hours.…”
mentioning
confidence: 99%
“…11 Pomalidomide pharmacokinetics have been well characterized both in healthy subjects and in subjects with relapsed and refractory MM. [16][17][18][19][20][21][22] Pomalidomide was absorbed with a maximum plasma concentration (C max ) at a median time (t max ) between 2.0 and 3.0 hours. Systemic exposure to a single dose of pomalidomide as determined from the area under the concentration-time curve (AUC) increased in an approximately dose-proportional manner up to 50 mg.…”
mentioning
confidence: 99%